The Role of Cognitive and Perceptual Loads in Inattentional Deafness - Causse, Mickaël; Imbert, Jean-Paul; Giraudet, Louise; Jouffrais, Christophe; Tremblay, Sébastien (Frontiers in Human Neuroscience, 2016)
The current study examines the role of cognitive and perceptual loads in inattentional deafness (the failure to perceive an auditory stimulus) and the possibility to predict this phenomenon with ocular measurements. Twenty participants performed ATC scenarios – in the Laby ATC-like microworld – guiding one (low cognitive load) or two (high cognitive load) aircraft while responding to visual notifications related to 7 (low perceptual load) or 21 (high perceptual load) peripheral aircraft. At the same time, participants were played standard tones which they had to ignore (probability = 0.80), or deviant tones (probability = 0.20) which they had to report. Behavioral results showed that 28.76 % of alarms were not reported in the low cognitive load condition and up to 46.21 % in the high cognitive load condition. On the contrary, perceptual load had no impact on the inattentional deafness rate. Finally, the mean pupil diameter of the fixation that preceded the target tones was significantly lower in the trials in which the participants did not report the tones, likely showing a momentary lapse of sustained attention, which in turn was associated to the occurrence of inattentional deafness.